Engineering the Interlayer Spacing by Pre‐Intercalation for High Performance Supercapacitor MXene Electrodes in Room Temperature Ionic Liquid (Adv. Funct. Mater. 33/2021). (17th August 2021) - Liang, Kun; Matsumoto, Ray A.; Zhao, Wei; Osti, Naresh C.; Popov, Ivan; Thapaliya, Bishnu P.; Fleischmann, Simon; Misra, Sudhajit; Prenger, Kaitlyn; Tyagi, Madhusudan; Mamontov, Eugene; Augustyn, Veronica; et al.
Abstract : Interlayer Spacing In article number 2104007, Michael Naguib and co‐workers report the engineering of interlayer spacing of multilayer MXene—by pre‐intercalation of pillars—to host large‐size cations of room temperature ionic liquids in between the layers, achieving high energy density supercapacitors. An optimum interlayer spacing of 2.2 nm (for pre‐intercalated Ti3 C2 ) allows for a capacitance of 257 F g −1 (1428 mF cm −2 and 492 F cm −3 ) over a 3.2 V potential window in 1‐ethly‐3‐methylimidazolium bis‐(trifluoromethylsulfonyl)‐imide electrolyte.